1997
DOI: 10.1016/s0014-5793(97)01213-1
|View full text |Cite
|
Sign up to set email alerts
|

Suramin enters and accumulates in low pH intracellular compartments of v‐sis‐transformed NIH 3T3 cells

Abstract: Using acridine orange as a reporter compound, we demonstrate that suramin enters and accumulates in low pH intracellular compartments (endosomes, lysosomes, and transGolgi complex) of normal and v-sis-transformed NIH 3T3 cells. The concentration of suramin in these acidic compartments is estimated to be > 150 μΜ, higher than the concentration known to completely inhibit interaction of the platelet-derived growth factor (PDGF) receptor and v-sis gene product. These results support the hypothesis that suramin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…Alternatively, these large, charged molecules might present reduced cell permeability owing to their size or charged residues, and might therefore only interfere with surface PrP. At least for suramin, uptake and intracellular localisation in low pH intracellular compartments (endosomes, lysosomes and TGN) in concentrations similar to those used in our studies have been described (Fransson et al, 1995;Huang et al, 1997). As the majority of the derivatives have similar molecular weights and similar numbers of sulphated substitutions as suramin, a certain cell permeability cannot be excluded.…”
Section: Discussionmentioning
confidence: 69%
“…Alternatively, these large, charged molecules might present reduced cell permeability owing to their size or charged residues, and might therefore only interfere with surface PrP. At least for suramin, uptake and intracellular localisation in low pH intracellular compartments (endosomes, lysosomes and TGN) in concentrations similar to those used in our studies have been described (Fransson et al, 1995;Huang et al, 1997). As the majority of the derivatives have similar molecular weights and similar numbers of sulphated substitutions as suramin, a certain cell permeability cannot be excluded.…”
Section: Discussionmentioning
confidence: 69%
“…Subsequently, Baghdiguian et al (20) performed quantitative auto-radiographic analysis revealing that in the absence of serum albumin labeled suramin was found to enter the human colon adenocarcinoma cells and distribute over the nucleus, the Golgi apparatus, and the mitochondria. In addition, using an indirect acridine orange reporter assay, Huang et al (21) reported that suramin enters and accumulates in low-pH intracellular compartments (endosomes, lysosomes, and transGolgi complex) of normal and v-sis-transformed NIH 3T3 cells. To facilitate the cellular analysis of suramin, we used a serum-starvation protocol developed by Baghdiguian et al (20) to increase the uptake of suramin and treated U2OS cells with this compound in concentrations ranging from 62.5 to 500 μM.…”
Section: Hts Identification Of Suramin As An Inhibitor Of Crl-mediatementioning
confidence: 99%
“…Human heparanase shows a strong tendency to localize to perinuclear granules (45). It has been reported that cells take up suramin via caveolae and transport it both to endosomes and the trans-Golgi as well as to the nucleus (46,47). Although degradation of HS by cell surface-located heparanase can be effectively inhibited by suramin (23), recycling Gpc-1 HS is only partially protected from degradation by suramin, because there is also an intracellular NO-dependent degradation (19,20).…”
Section: Suramin Treatment Causes Accumulation Of S-nitrosylatedmentioning
confidence: 99%